La inscripción de nacimiento y las técnicas de reproducción humana asistida, en el cantón Guaranda, año 2023. - Lemache Prado Heidy Rashel (2025)
The work is entitled: “Birth registration and assisted human reproduction techniques in the canton Guaranda, year 2023”. It focuses on knowing what are the requirements demanded by the law for the registration of the birth of the new human being, pointing out that the regulations, Ecuadorian does not establish any type of requirement to those procreated through one of the new techniques of assisted human reproduction. This is a real problem since Ecuador is supposed to be a Constitutional State of Law that guarantees the right to identity and in such way the right to know one's own origin, however, since there is no information or identification data of the procreated through one of these new techniques, in reality the fulfillment of these rights would not be verified. Thus, the formulation of the research problem is: How do assisted human reproduction techniques affect birth registration in the canton of Guaranda, year 2023? Taking into account that this is the question that guides all the research work, it should be insisted that all the efforts of the researcher should be directed to answer this question. Thus, the general objective of the present work is: To analyze the assisted human reproduction techniques and their repercussion on birth registration in the Guaranda canton, year 2023. Emphasizing that the specific objectives of the work are steps that should address the general objective, the work will initially focus on analyzing the birth registration process, the new assisted human reproduction techniques and the best interests of the child. Within the methodological framework, the research was based on a mixed approach, using qualitative data to analyze documents such as regulations, doctrines and jurisprudence. The method used throughout was mainly the interpretative one, to analyze and relate the documented information, contrasting the provisions of the law with the different theories, to finally study what has been proposed in the jurisprudence related to the subject. The research collected information through the techniques of documentary review and surveys, using the respective guides. Finally, the research arrived at the main conclusions and recommendations. It also made a proposal for regulatory reform. Key words: identity, right to know one's origin, assisted reproduction participants, identification data.